2007
DOI: 10.3758/bf03193915
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of spatial attention to words in central and peripheral vision

Abstract: Four perceptual identification experiments examined the influence of spatial cues on the recognition of words presented in central vision (with fixation on either the first or last letter of the target word) and in peripheral vision (displaced left or right of a central fixation point). Stimulus location had a strong effect on word identification accuracy in both central and peripheral vision, showing a strong right visual field superiority that did not depend on eccentricity. Valid spatial cues improved word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 65 publications
12
45
2
Order By: Relevance
“…Finally, the results of the present study revealed an RVF bias that is consistent with prior research showing visual field asymmetries in visual word recognition (see Ducrot & Grainger, 2007, for a review) and masked repetition priming effects (Marzouki et al, 2007). Attentional asymmetries induced by reading habits provide a unified account of these different visual field effects.…”
Section: Attention and Readingsupporting
confidence: 92%
“…Finally, the results of the present study revealed an RVF bias that is consistent with prior research showing visual field asymmetries in visual word recognition (see Ducrot & Grainger, 2007, for a review) and masked repetition priming effects (Marzouki et al, 2007). Attentional asymmetries induced by reading habits provide a unified account of these different visual field effects.…”
Section: Attention and Readingsupporting
confidence: 92%
“…We think that our results better fit with the attentional bias theory. 2 First, we also obtained a larger asymmetric effect of the distractor with the increase in eccentricity from 1.4 to 1.9 (similarly to Ducrot & Grainger, 2007, who compared foveal and parafoveal words), and this is in agreement with the gradient theory of attention developed by Kinsbourne (1993). Second and most importantly, the asymmetric attentional effect was no larger in adults than in children.…”
Section: Attentional Biassupporting
confidence: 86%
“…Attentional differences may exist depending on the word's exact location in the visual field (Carrasco, Williams, & Yeshurun, 2002), and parafoveally presented words may require more attention than foveally presented words (Ducrot & Grainger, 2007). When words were displaced from the center of the visual field to a hemifield, Cohen, Dehaene, Vinckier, Jobert, and Montavont (2008) found greater activity in the bilateral posterior intra-parietal cortices and in mesial posterior parietal regions (including precuneus), which have all been involved in visual attention tasks.…”
Section: Attention In Word Readingmentioning
confidence: 98%
See 1 more Smart Citation
“…A complementary account could be derived from a standard finding in the literature on visual word recognition: Words presented to the right visual field are easier to recognize than words presented to the left visual field (Lindell & Nicholls, 2003). A possible explanation for this asymmetry is that fixations on the left half of the word are less "damaging" than fixations on the right half, because attention can be allocated more rapidly to the right than to the left in people who are trained to read in that direction (see Ducrot & Grainger, 2007). Note that in condition P5 of our experiment, the first fixation was on the last letter of the word, which was thus displayed in the left visual field.…”
Section: Author Notementioning
confidence: 99%